Impact of parboiling processing conditions on rice characteristics - Hunt, Martha (Kansas State University, 2019)
Parboiling rice is the process of soaking, steaming, and drying prior to milling. One of the primary advantages to parboiling is the potential to increase head rice yield. Head rice are the kernels that are at least three-fourths intact after milling and are more economically valuable than broken kernels. Parboiling also migrates of nutrients from the exterior bran layer to the interior of the rice kernel during soaking and steaming, thereby improving the nutritional value of the rice post-milling. Parboiling causes physical changes to the rice kernel, such as kernel hardening and pasting properties that lead to longer cook times and different eating texture. One quality of parboiled rice that is monitored and can be slightly disadvantageous is color. Parboiled rice is typically yellow and darker in color than unparboiled rice, and severity of parboiling conditions can increase the color to defect levels if not controlled. Soaking is the first stage of parboiling and the primary objective is to obtain uniform absorption of water to about 30%, which prepares the rice kernel for starch gelatinization. Steaming is the second stage of parboiling and targets fully gelatinizing the starch, sealing fissures in the kernel endosperm that might otherwise break apart during milling. Drying is the third stage of parboiling and requires lowering the moisture content gently to attain optimal quality for storage and milling (typically between 12-14%). Milling is the next stage of production after parboiling and removes the bran layer and hull, resulting in saleable rice products. Parboiling can result in advantages for millers, such as: improved head rice yields, improved nutritive content rice that can be marketed to customers, and different pasting properties that can make unique rice ingredients, like longer cooking times and firmer kernels. Research on the effectiveness of the rice parboiling process starts with understanding the rice qualities and structural composition going into processing, and then applying that knowledge to optimize parboiling processing parameters. Research on adjusting processing methods compared to the traditional approach can focus on pre-processing applications, like heat-moisture treatment prior to parboiling or pre-steaming. Studies can also focus on modifying conditions during the parboiling process, such as; the application of IR heat during steaming and soaking, continuous steaming, and fluidized bed-drying. Ultimately, researchers seek to modify the traditional parboiling process to minimize processing time and energy requirements, while concurrently increasing head rice yields and desirable rice characteristics.
Keywords: Parboiling rice